Ovoid palatal patch: a clue to anti-TIF1γ dermatomyositis - Franciosi, Ellen (BMJ Case Rep, 2020)
An 80-year-old woman presented with a several-year history of progressive hair loss and scalp pruritus. No other rashes or muscle weakness were noted on examination. Scalp biopsy showed interface dermatitis, dense perivascular and periadnexal lymphocytic infiltrate, mucin and scarring alopecia. Laboratory analysis did not show evidence of myositis. The patient was started on hydroxychloroquine for possible cutaneous lupus erythematosus. On follow-up, she presented with a new violaceous rash on the superior eyelids and a well-defined oval patch on the mid-hard palate suspicious for dermatomyositis. Myositis-specific autoantibodies revealed presence of anti-transcriptional intermediary factor-1γ (anti-TIF1γ) in the serum. Anti-TIF1γ autoantibody-positive dermatomyositis is a newly recognised subtype of dermatomyositis that is highly associated with amyopathic disease and has an increased risk of malignancy, making prompt diagnosis crucial. This case highlights the utility of a thorough oral exam in patients suspected to have connective tissue disease as the distinctive ovoid palatal patch is nearly pathognomonic for anti-TIF1γ dermatomyositis.